Barriers to Access: A Feminist Analysis of Medically Assisted Dying and the Experience of Marginalized Groups. (November 2021) - Sikka, Tina
In this article, I argue that a holistic strategy is needed to ascertain how implicit bias, on the part of health-care providers, and structural impediments work together to produce significant barriers to access to medical assistance in dying for marginalized groups—particularly those experiencing intersecting or interlocking forms of identity-based oppressions. In doing so, I also make the case that this kind of primary, patient-centered, and institutional research could benefit from the insights of critical feminism and materialist feminist theory by highlighting and challenging inequalities, opening up debate, and exploring new forms of knowledge production. It also offers a way to shape future research of medical assistance in dying, as it relates specifically to the study of how overlapping forms of structural and interpersonal marginalization (e.g., implicit bias), inclusive of race, gender, class, ethnicity, dis/ability, sexuality, and so on are expressed and experienced.